2012
DOI: 10.1186/1476-511x-11-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific association of ACAT-1 rs1044925 SNP and serum lipid levels in the hypercholesterolemic subjects

Abstract: BackgroundAcyl-CoA:cholesterol acyltransferase (ACAT) is a key enzyme in cellular cholesterol homeostasis and in atherosclerosis. The cellular cholesterol efflux correlated with serum high-density lipoprotein cholesterol (HDL-C) concentrations has shown to be impaired in hyperlipidemic mice. The present study was carried out to clarify the association of ACAT-1 rs1044925 single nucleotide polymorphism (SNP) and serum lipid levels in the hyperlipidemic subjects.MethodsA total of 821 unrelated subjects (hyperlip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
(40 reference statements)
2
15
0
Order By: Relevance
“…At the same time, ω -3 PUFAs show a direct regulation on gene expression vianuclear receptors and transcription factors, which are in turn modulated by cytoplasmic lipid binding proteins transporting these fatty acids into the nucleus. Regulation of ω -3 PUFAs on gene expression could explain the altered protein expression that we reported on the RTT plasma proteome and is in line with previous findings in adult smokers following a short course (i.e., 5 weeks) of ω -3 PUFAs enriched diet [12]. In this latter study, proteins related to the antioxidant, anti-inflammatory, and antiatherosclerotic properties of HDL were upregulated, in contrast with down-regulation of complement activation and APR proteins.…”
Section: Discussionsupporting
confidence: 92%
“…At the same time, ω -3 PUFAs show a direct regulation on gene expression vianuclear receptors and transcription factors, which are in turn modulated by cytoplasmic lipid binding proteins transporting these fatty acids into the nucleus. Regulation of ω -3 PUFAs on gene expression could explain the altered protein expression that we reported on the RTT plasma proteome and is in line with previous findings in adult smokers following a short course (i.e., 5 weeks) of ω -3 PUFAs enriched diet [12]. In this latter study, proteins related to the antioxidant, anti-inflammatory, and antiatherosclerotic properties of HDL were upregulated, in contrast with down-regulation of complement activation and APR proteins.…”
Section: Discussionsupporting
confidence: 92%
“…However, plasma concentrations of HDL-C and ApoAI in subjects with the 77G-A variant were significantly higher than in hyperlipidemic subjects without the variant. In a previous study, we also showed that rs1044925 was associated with increased serum HDL-C only in hyperlipidemic subjects [24]. These data suggest that the ACAT-1 variants may be associated with reduced ACAT-1 protein expression and influence cellular cholesterol efflux on hyperlipidemia, thereby playing an important role in atherosclerosis progression.…”
Section: Discussionsupporting
confidence: 61%
“…Genomic DNA was isolated from peripheral blood leukocytes using the phenol-chloroform method [24,27]. Genotyping of rs1044925 was performed by polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was isolated from peripheral blood leukocytes using the phenol-chloroform method [31, 32]. The extracted DNA was stored at 4 °C until analysis.…”
Section: Methodsmentioning
confidence: 99%